Reading Skills Used in English Textbook - Suyadi Suyadi; Husnaini Husnaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This article investigates a reading skill content in English textbook used at a state senior high school from the point of view its variety, exploitability, suitability, length of text, readability, and authenticity of texts. A representation theory was used to explore the key issue of a textbook. A multimodal discourse analysis is applied, in more specifically through verbal analysis and visual analysis of the texts within the textbook. The results of analysis reveal that there are seven reading texts with different variety namely narrative, expository, speech, play script, and recount text. There is one text that is not suitable with characteristics of a book length, and the rest of the texts are met its variety, exploitability, readability, and its authenticity. Therefore, further studies with a different analysis are required to achieve deeper information about how English textbook used in Indonesia can implement the characteristics of international standard.